Unique features of conventional and nonconventional introns in Euglena gracilis - Gao, Pingwei; Zhao, Yali; Xu, Guangjie; Zhong, Yujie; Sun, Chengfu (BMC genomics, 2024)
Nuclear introns in Euglenida have been understudied. This study aimed to investigate nuclear introns in Euglenida by identifying a large number of introns in Euglena gracilis (E. gracilis), including cis-spliced conventional and nonconventional introns, as well as trans-spliced outrons. We also examined the sequence characteristics of these introns. A total of 28,337 introns and 11,921 outrons were identified. Conventional and nonconventional introns have distinct splice site features; the former harbour canonical GT/C-AG splice sites, whereas the latter are capable of forming structured motifs with their terminal sequences. We observed that short introns had a preference for canonical GT-AG introns. Notably, conventional introns and outrons in E. gracilis exhibited a distinct cytidine-rich polypyrimidine tract, in contrast to the thymidine-rich tracts observed in other organisms. Furthermore, the SL-RNAs in E. gracilis, as well as in other trans-splicing species, can form a recently discovered motif called the extended U6/5' ss duplex with the respective U6s. We also describe a novel type of alternative splicing pattern in E. gracilis. The tandem repeat sequences of introns in this protist were determined, and their contents were comparable to those in humans. Our findings highlight the unique features of E. gracilis introns and provide insights into the splicing mechanism of these introns, as well as the genomics and evolution of Euglenida.